2010
DOI: 10.1007/s00705-010-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel hepatitis B virus subgenotype C10 in Nusa Tenggara, Indonesia

Abstract: Six novel subgenotypes (B7, B8, C6, C8, C9, and D6) within three hepatitis B virus (HBV) genotypes (B-D) were recently identified in Indonesia. To further characterize HBV in this country, 18 HBV-viremic samples obtained from blood donors in Nusa Tenggara, Indonesia, were subjected to phylogenetic analysis of an 1.6-kb partial or full-length sequence. Thirteen HBV isolates were classified into genotype B with four distinct subgenotypes [B3 (n = 2), B5 (n = 1), B7 (n = 4), and B8 (n = 6)], followed by 4 HBV iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Based on a molecular analysis of a portion of the HBV preS2/S gene, most HBV isolates belonged to genotype B3. This finding supports a previous finding that B3 is the major genotype in Indonesia [32][33][34]. The nucleotide sequences of the seven HBV isolates had higher homology to foreign strains retrieved from the Genbank/EMBL/DDBJ database, suggesting that foreign HBV strains are occasionally introduced into Indonesia.…”
Section: Discussionsupporting
confidence: 89%
“…Based on a molecular analysis of a portion of the HBV preS2/S gene, most HBV isolates belonged to genotype B3. This finding supports a previous finding that B3 is the major genotype in Indonesia [32][33][34]. The nucleotide sequences of the seven HBV isolates had higher homology to foreign strains retrieved from the Genbank/EMBL/DDBJ database, suggesting that foreign HBV strains are occasionally introduced into Indonesia.…”
Section: Discussionsupporting
confidence: 89%
“…It has been also reported from Morocco and Russia and Baltic region [57,58,74]. D6: It has been reported as a rare subgenotype from Indonesia, Kenya, Russia and Baltic region [22][23][24][25][26]54,55,74].…”
Section: Subgenotypes Of Genotype Dmentioning
confidence: 87%
“…However, genotype C and B are prevalent and D is rare (around 1%) in Eastern China and among genotype D, D1 and D2 are noted [10]. The subgenotype distribution of genotype D is also different among parts of India [24][25][26][27][28][29][30]. Similarly subgenotype studies may help tracking the movements of some population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been reported that in Indonesia some new HBV genotypes have been elucidated (Lusida et al, 2008, Mulyanto et al, 2009, 2010, 2012. This means that efforts to prevent the spread of HBV in Indonesia will be more effective if we can provide the components to develop diagnostic kits derives from the local germ plasma.…”
Section: Resultsmentioning
confidence: 99%